Characterization of Neuwiedin, a new disintegrin from Bothrops neuwiedi venom gland with distinct cysteine pattern. (15th September 2015) - Lima-dos-Santos, I.; Della-Casa, M.S.; Portes-Junior, J.A.; Calabria, P.A.L.; Magalhães, G.S.; Moura-da-Silva, A.M.
Abstract: Disintegrins are cysteine-rich toxins containing the RGD motif exposed in a loop that binds integrins such as αIIb β3, α5 β1 and αv β3 . The flexibility of the RGD loop, controlled by the profile of the cysteine pairs and the residues flanking the RGD sequence, are key structural features for the functional activity of these molecules. Recently, our group reported a transcript in the venom gland of Bothrops neuwiedi corresponding to a new P-II SVMP precursor, BnMPIIx, in which the RGD-binding loop includes many substituted residues and unique cysteine residues at the C-terminal. In this paper, we obtained the recombinant disintegrin domain of BnMPIIx, Neuwiedin, which inhibited ADP-induced platelet aggregation, endothelial cell adhesion to fibrinogen and tube formation in Matrigel with no particular selectivity to αIIb β3 or endothelial cell integrins. This value was also comparable to the inhibition observed with other recombinant disintegrins with conserved cysteine positions and residues in RGD loop. In this regard, Neuwiedin is an important component to understand the functional relevance of the diversity generated by accelerated evolution of venom toxins as well as to find out eventual new disintegrin-dependent targets that may be approached with disintegrins. Highlights: Neuwiedin is a Bothrops neuwiedi disintegrin domain with unique cysteine pattern. Recombinant Neuwiedin was obtained using pMST3 bacterial expression vector. Neuwiedin disintegrin activity was similar to other recombinant disintegrins. The structural diversity of venom toxins may not correlate to function diversity.